The Synthesis and characterization of hydrophilic gold nanoparticles via a DEN-MPC method and their evaluation as biphasic catalysts - Cloete, Jezreel (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.